A method to include component condition and substation reliability into distribution system reconfiguration. (July 2019) - Sarantakos, Ilias; Greenwood, David M.; Yi, Jialiang; Blake, Simon R.; Taylor, Phil C.
Highlights: Component condition and S/S reliability are used to inform DSR. S/S reliability depends on asset condition, S/S configuration and upstream network. Condition-based failure rates are derived from component health indices. Customer interruption costs are a function of outage duration and customer type. The proposed method is successfully demonstrated on two distribution systems. Abstract: Component condition and substation (S/S) reliability have a material impact on the cost of customer interruptions in electricity distribution systems (DSs). However, these factors are not usually considered within distribution system reconfiguration (DSR) problem formulations, because of the lack of a readily available methodology. This paper presents such a method, making use of component condition scores which are now mandatory for distribution system operators (DSOs) in the UK. Based on these condition scores, condition-based failure rate can be calculated for each component. S/S reliability is a function of component condition, S/S configuration and the network upstream of the S/Ss. The reliability of the S/S then has an impact on the reliability indices of each load point (LP) it supplies. These factors are combined to deliver a better informed algorithm for DSR, which is verified through its application on two DSs. The annual savings, compared to the formulation that neglects component condition and S/S reliability, can be in the order of tens of thousands of U.S. dollars for a single DS.